Identifikasi Awal Bentuk Bangunan di Situs Candi Ronggeng - Endang Widyastuti; Nanang Saptono (Kemendikbud, 2020)
The research that was conducted at Ronggeng Temple has not yet describe the complete shape of the building. The studies that have been carried out only classify the type of temples as a simple building. This article is attempting to describe the shape of Ronggeng Temple based on the results of excavation. This article uses the results of excavations that have been carried out in 2019 as a data, and then compared it with the results of previous excavations. The data is then analyzed toget an overview of the shape of Ronggeng Temple. The excavation result shows that Ronggeng Temple is a short fence with an object of worship in the middle of the site. The objects of worship are in the form of yoni and nandi was placed protectively under a roof supported by pillars with a round shape stone footsteps.